Strategy analysis of directoring of the ketoprak event at LPP RRI Semarang - Sri Hastuti (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2022)
LPP RRI Semarang has a function not only to provide information and entertainment but also to contribute to the preservation of local culture by presenting various cultural arts programs such as